PERENCANAAN ULANG SUPER STRUKTUR DENGAN STRUKTUR FLAT SLAB PADA GEDUNG TOKO DAN GUDANG JALAN RAYA PURA DEMAK DENPASAR BALI - DEWA GEDE ARI KAMA GUNA KAMA GUNA; I Putu Ellsa Sarassantika; Cokorda Agung Yujana (UKI Press, 2025)
This study was conducted to analyze the performance of multi-story building structures using a flat slab system with drop panels, both in single and adjacent configurations. The research was motivated by Indonesia’s high seismic activity and the growing need for efficient and easily constructed structural systems that also provide aesthetic benefits. The main objective was to evaluate and compare the lateral displacement behavior of both structural models and assess their compliance with the drift limits specified in SNI 1726:2019. The analysis was performed through numerical modeling using ETABS software, with load combinations following SNI 1727:2020 for minimum design loads and SNI 2847:2019 for reinforced concrete strength provisions. The structural models consisted of a 200 mm thick flat slab and a 300 mm thick drop panel, supported by beams and columns designed to meet flexural and shear capacity requirements. The analysis results indicated that the maximum displacement was 34.584 mm in the X direction and 12.832 mm in the Y direction, both within the allowable drift limits. The adjacent building model exhibited average lateral displacements 1.25 times smaller in the X direction and 3.75 times smaller in the Y direction compared to the single structure, indicating a stiffness improvement due to inter-building interaction. All structural components, including the 7.6-meter-deep pile foundation, satisfied the strength and stability criteria. It was concluded that the flat slab system with drop panels is structurally efficient and seismically safe, providing a reliable alternative for building design in earthquake-prone regions.